2012
DOI: 10.1039/c2lc40084g
|View full text |Cite
|
Sign up to set email alerts
|

Passive control of cell locomotion using micropatterns: the effect of micropattern geometry on the migratory behavior of adherent cells

Abstract: Directed cell migration is critical to a variety of biological and physiological processes. Although simple topographical patterns such as parallel grooves and three-dimensional post arrays have been studied to guide cell migration, the effect of the dimensions and shape of micropatterns, which respectively represent the amount and gradient of physical spatial cues, on cell migration has not yet been fully explored. This motivates a quantitative characterization of cell migration in response to micropatterns h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 50 publications
1
35
0
1
Order By: Relevance
“…Cells cultured on TCPS were in the middle of these regions with a P of 60 min and an S of 0.18 mm/min. This compares well with other literature values of~0.2 mm/min for NIH/3T3 cells [41],~0.17 mm/min for primary fibroblasts [42], and directional persistence of~40 min for secondary fibroblasts [43].…”
Section: Migrationsupporting
confidence: 89%
“…Cells cultured on TCPS were in the middle of these regions with a P of 60 min and an S of 0.18 mm/min. This compares well with other literature values of~0.2 mm/min for NIH/3T3 cells [41],~0.17 mm/min for primary fibroblasts [42], and directional persistence of~40 min for secondary fibroblasts [43].…”
Section: Migrationsupporting
confidence: 89%
“…The vectors indicated that net motion was isotropic and random on flat surfaces, whereas it was rectified toward the positive y axis on the ratchet pattern. Previous gradient-free strategies relied on cell confinement, either chemical (12)(13)(14)(15) or physical (16)(17)(18). However, here we show that cells on an asymmetric topographical pattern, with no restriction in adhesiveness or physical confinement, moved in the direction imposed by the features of the ratchet itself.…”
Section: Directing Cell Migration With a Ratchet-like Topographymentioning
confidence: 60%
“…Previous studies achieved biased cell motion by asymmetric patterns, either chemical (12)(13)(14)(15) or physical (13,(16)(17)(18), that induced cell polarization by means of confining cells and restricting their motion to one-dimensional. Geometrical asymmetries in the pattern design amplified natural differences in lamellipodia activity at the front and the rear of a polarized cell, leading to directed motion (12)(13)(14)(15)17,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Micropatterning techniques have become an established tool for researchers interested in single-cell functions and dynamics [1][2][3][4][5][6][7] and the collective behavior of small cell assemblies and tissues [8][9][10] . Their significance for today's cell science arises from the fact that they provide direct control over the shape and functionality of the cell's environment on a microscopic scale.…”
Section: Introductionmentioning
confidence: 99%